THE EFFECT OF THE LEARNING START WITH A QUESTION (LSQ) LEARNING MODEL ON THE LEARNING OUTCOMES OF SCIENCE STUDENTS IN HUMAN DIGESTIVE SYSTEM - Putri, Aulia Musva; Diliarosta, Skunda (Universe, 2025)
Learning using a scientific approach is ideally accompanied by the activeness of students and students' interest in reading, with active and direct participation of students in learning is able to increase students' understanding of learning material, this will later be in line with the achievement of student learning outcomes, but in reality there are still many students who have scores below the Minimum Completeness Criteria (KKM). The purpose of this study was to find out whether there was an effect of the Learning Start With A Question learning model on digestive system material on the learning outcomes of Class VIII science students at SMP N 29 Padang. This type of research is using quasi-experimental design (Quasi Experimental Design). The research design was the Pretest-Posttest Nonequivalent Control Group Design. The sample selection technique in this study was a purposive sampling technique. The subjects in the study consisted of two sample classes, namely the control class and the experimental class which consisted of 32 people in each class. The results showed that there was an influence of the Learning Starts With a Question (LSQ) Learning Model at SMP N 29 Padang which had an effect on students' science learning outcomes in the cognitive domain, this can be seen from the results of the hypothesis test where tcount > ttable means tcount 2,19 > 1 .67 which indicates that H0 is rejected and H1 is accepted, and there is an influence that the Learning Starts With a Question (LSQ) Learning Model at SMP N 29 Padang has an effect on students' natural science learning outcomes in the cognitive domain, as well as affective assessment of the four aspects of class the experimental sample has an average score that is higher compared to the control class so that it can be concluded that the LSQ model affects the academic achievement of students in the affective domain.